Peran Fee-Based Income sebagai Mediator antara Layanan Digital Perbankan dengan Kinerja Keuangan di Bank Swasta yang Terdaftar di BEI - Saur Costanius Simamora; Ikaputra Waspada (Research Center and Case Clearing House PPM School of Management, 2023)
The study analyzed the effect of mobile banking, internet banking, and e-wallet on ROA through fee-based income from digital services at private banks listed on the IDX. The objectives of this study are (1) to the effect of mobile banking, internet banking, and e-wallet on fee-based income, (2) to analyze the influence of mobile banking, internet banking, and e-wallet on return on asset (ROA) (3) to Formulate managerial implications for increasing the use of digital service at private bank listed on the IDX. The data in this study were analyzed using Structural Equation Modeling (SEM) Pls with 396 data with a sampling technique using purposive sampling in 2019-2021. The indicators used were the number of users, the number of transactions, and the nominal transactions. The results show that e-wallet has an effect on fee-based income and also has an effect on ROA. However, mobile and internet banking do not affect fee-based income and ROA. The managerial implications that can be given are maintaining the performance of e-wallet services, improving the performance of mobile banking and internet banking services with technology features, and promoting services to old and new customers at private banks listed on the IDX.